Optimizing Patient Blood Management: Successful Intraoperative Cell Salvage During Cesarean Hysterectomy for Placenta Accreta Spectrum - A Case Report - Fathimah Azzahra; Ruddi Hartono (HM Publisher, 2026)
Introduction: Placenta accreta spectrum disorders represent a critical maternal health concern with a high risk of massive obstetric hemorrhage, which conventionally necessitates substantial allogeneic blood transfusion. Intraoperative cell salvage serves as a highly efficient autotransfusion alternative within modern patient blood management frameworks. Case presentation: A 37-year-old female (Gravida 4, Para 1) at 37-38 weeks of gestation presented with total placenta previa and a Placenta Accreta Index score of 6, correlating to a 69% probability of placenta accreta. A transperitoneal profunda cesarean section with subsequent hysterectomy was planned. A combined spinal-epidural anesthesia technique was utilized, justified by favorable airway metrics and supported by a proactive massive transfusion protocol. Surgical estimated blood loss was 3,500 mL. An intraoperative cell salvage device processed 2,438 mL of shed fluid, which included 1,000 mL of surgical irrigation. This yielded 451 mL of washed packed red blood cells that were successfully reinfused. The patient’s hemodynamics were stabilized using a continuous norepinephrine infusion. The patient received zero allogeneic blood products throughout her admission. Hemoglobin levels were maintained from 10.1 g/dL preoperatively to 9.2 g/dL at discharge. Postoperative coagulation profiles remained stable. The patient was discharged on postoperative day 5 without complications. Conclusion: The application of intraoperative cell salvage in major obstetric surgery is demonstrably safe and clinically beneficial. This technology provides a resource-optimized alternative to allogeneic transfusion.